Os físicos e a medicina da alma no Orto do Esposo - Marisa das Neves Henriques (Medievalista)
In Orto do Esposo, a book from the end of the XIVth century or from the beginning of the XVth century, that explores monastic spirituality, one can find several physicians, all of them having a special role, in part due to the close relation between the spheres of profane and sacred.Nevertheless, the priority is taking care of the ill soul, instead of worrying too much about body. Health is synoym of salvation, so there is no secular science that could stand such noble project.Christ, the caelestis medicus, and the holy Bible, are the protagonists of a soul’s medicine that Orto do Esposo prescribes in detail. In these matter, the portuguese text reflects the lesson of St. Bernard's sermons on the Canticle of Canticles. Through the respect to the monastic model, it will be possible to find recipes to promote soul therapy and restauratio post mortem.